California Supreme Court Justice Wiley Manuel Visits Office of Fresno County Counsel - Watkins, Howard::::::::: (1979)
Louis Lozano, Jerome Behrens, Justice Wiley Manuel, County Counsel Floyd Viau, James Waterman Office law library in Hall of Records building 3rd floor